2021
DOI: 10.22541/au.161235327.73809250/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence of viral survival in representative volumes of feed and feed ingredients during long-distance commercial transport across the continental United States

Abstract: The hypothesis that feed ingredients could serve as vehicles for the transport and transmission of viral pathogens was first validated under laboratory conditions. To bridge the gap from the laboratory to the field, this current project tested whether three significant viruses of swine could survive in feed ingredients during long-distance commercial transport across the continental US. One-metric ton totes of soybean meal (organic and conventional) and complete feed were spiked with a 10 mL mixture of PRRSV 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In their recent 23-days bulk transport study, Dee et al (2021) found that RNA viruses (PEDV, SVA, and PRRSV) were present in one tonne totes of conventional soybean meal (average Ct values of 34.6, 35.7, and 34.9, respectively) and organic soybean meal (average Ct values of 37.6, 35.3 and 34.1, respectively) using real time RT-PCR. When evaluating totes with complete feed, SVA was recovered in only one tote (Ct value of 35.5), with no detectable PEDV or PRRSV found in inoculated totes using the same real time RT-PCR methodology.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In their recent 23-days bulk transport study, Dee et al (2021) found that RNA viruses (PEDV, SVA, and PRRSV) were present in one tonne totes of conventional soybean meal (average Ct values of 34.6, 35.7, and 34.9, respectively) and organic soybean meal (average Ct values of 37.6, 35.3 and 34.1, respectively) using real time RT-PCR. When evaluating totes with complete feed, SVA was recovered in only one tote (Ct value of 35.5), with no detectable PEDV or PRRSV found in inoculated totes using the same real time RT-PCR methodology.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating totes with complete feed, SVA was recovered in only one tote (Ct value of 35.5), with no detectable PEDV or PRRSV found in inoculated totes using the same real time RT-PCR methodology. However, when pigs were fed contaminated complete feed, they developed a positive PEDV infection, but were negative for PRRSV, suggesting that PEDV remained infectious in a feed matrix after a trans-continental journey, while PRRSV did not (Dee et al, 2021). These observations are not surprising because of the lack of adequate sensitivity of commonly used diagnostic assays to characterize the quantity of viable virus capable of causing infection (Shurson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations